Utilizing X-Ray Flourescence (XRF) analysis for identifying C3 sugar syrup adulteration in honey - Pagalan, Mark John C. (College of Home Economics, University of the Philippines Diliman, 2023)
This study sought to address the challenge of detecting C3 sugar syrup adulteration in honey, an issue that current adulteration detection methods struggle with. Due to limited research on C3 sugar syrup adulteration and multi-element analysis, this investigation aimed to employ portable Energy-Dispersive X-ray Fluorescence (pXRF) to examine honey samples adulterated with C3-derived sugar syrups, specifically beet sugar syrup, rice syrup, and coconut sap syrup. The goal was to evaluate the efficacy of this method in identifying these particular adulterants. The specific objectives of the study were threefold: (1) determine and quantify the multi-elements in honey samples by pXRF; (2) statistically differentiate and analyze pure honey samples and pure C3 adulterants using boxplot and univariate analysis; and (3) determine reliable elements for detection of adulteration through logistic regression using machine learning algorithm. The findings revealed the presence of 46 elements in both pure honey and pure C3 adulterants. Magnesium was the most prevalent element in both pure honey and two of the C3 adulterants, with concentrations of 0.5149% in honey, 0.4533% in rice syrup, and 0.4096% in beet sugar syrup. However, in coconut syrup, chlorine emerged as the dominant element, accounting for 1.4498% of its composition. There was a significant distinction between pure honey and pure C3 adulterants in chlorine, potassium, and palladium, supported by a p-value 0.0010, <0.0001, 0.0029, respectively, which are less than p<0.05. A logistic regression model was developed, demonstrating 86% accuracy, with the element Cl as the most reliable element for differentiation (96.01% accuracy). These results suggest that pXRF analysis, particularly the measurement of chlorine content, could be a promising and reliable method for detecting honey adulteration with C3 sugar syrups.